Effect of addition of antimicrobial triclosan on selected properties of water-activated glass ionomer cement - W. Kupka, Tomasz; Nowak, Joanna; Szczesio, Agata; Kopacz, Karolina; Fronczek-Wojciechowska, Magdalena; Sokołowski, Jerzy (Journal of Stomatology, 2016)
Introduction. Failure of dental restorations is commonly associated with residual infected dentine underneath. Dental materials containing antimicrobials may overcome the problem of recurrent caries without jeopardizing their physicomechanical characteristics. Aim of the study. To evaluate hardness and diametral tensile strength (DTS) of a water-activated glassionomer (WAGIC) enriched with increasing mass concentration of triclosan (TRC) – the antimicrobial agent. Material and methods. TRC was added to the powder of WAGIC in weight concentrations of 0.5%, 1.0%, 1.5%, 2.0% served as experimental groups, and 0.0% as a control group, respectively. In each group two subgroups were defined to record Vickers hardness (HV0.3/15) and DTS after 1 and 24 hours of storage in distilled water. Shapiro-Wilk test of normality, parametric (F-test or t-test) or non-parametric (Kruskal-Wallis test or Mann-Whitney test) were used for the purpose of statistical analysis (p = 0.05); the equality of variance was checked with Levene’s test. Results. HV0.3/15 was significantly higher after 24 h than after 1 h. In both cases addition of 0.5 % of TRC caused significant decrease of hardness. DTS values were significantly higher after 24 h with addition of 0.5 % TRC, but generally it was slightly decreased in comparison to the control group. Conclusions. Except 0.5 % TRC, there was no negative influence of antimicrobial addition on HV0.3/15 and DTS, so TRC does not deteriorate strength of WAGIC.